新加坡华人威胁面子情况下语码转换的语用功能研究 = A study on the pragmatics of code-switching during face-threatening situations in Singaporean Chinese's conversations - 吴思琪 Goh, Alena Si Qi (Nanyang Technological University, 2024)
新加坡作为一个多元文化的社会，语码转换是人人必备的重要技能，也是一个常见的现象。威胁面子的情况在日常交际中经常发生，在新加坡这个多语社会，语码转换在应对威胁面子的情况扮演重要角色。因此，本文探讨了新加坡华人日常交流中，威胁面子情况时的语码转换的语用功能，希望能够通过其功能揭示其实际应用价值，并且为新加坡的语码转换研究提供新的视角以及有价值的参考。本文通过视频录像和谈话类节目 Gen Z Decodes 收集语料，并采取话语分析的方式进行分析。通过深入的研究，本文发现在威胁面子的情况下，新加坡华人的语码转换有维护自己或他人面子、调整人际关系以及表达视角转换的功能，这些功能能够帮助新加坡华人解除或避免恶化威胁面子的情况。本文也发现新加坡华人的语码转换在应对威胁面子的情况时，结合其他话语特征或行为可以让语码转换的效果更为显著。这项研究对于语码转换在维护社会和谐的应用具有重要意义。 Singapore, as a multicultural society, sees code-switching as an essential skill for everyone, making it a common phenomenon. Face-threatening situations occur frequently in daily communication, and in this multilingual society, code-switching plays a crucial role in dealing with such situations. Therefore, this paper explores the pragmatic functions of code-switching employed by Singaporean Chinese when they encounter face-threatening situations in their everyday communication. This paper hopes to reveal the practical value of code-switching through the functions it has. Moreover, this paper also aims to contribute a new perspective and valuable insights to the study of code-switching in the Singaporean context. This paper collects data from video recordings and a talk show called Gen Z Decodes, and the data is analysed using discourse analysis. Through in-depth research and analysis, the findings indicate that code-switching used by Singaporean Chinese in face-threatening situations has functions of maintaining the speaker or listener’s face, adjusting interpersonal relationships, and expressing perspective shifts. These functions help Singaporean Chinese to relieve or prevent the escalation of face-threatening situations. Additionally, the study highlights that when code-switching is combined with other discourse features or behaviours, its effects become more pronounced in handling face-threatening situations. Overall, this study has important significance for the application of code-switching to maintain social harmony.